Creating Awareness about Cleanliness and Hand Hygiene among Students at Primary Level - Dr. Wajiha Kanwal; Dr. Cedric Aimal Edwin; Dr. Abid Ahmad; Uroosa Rafaqat (Journal of Management Practices, Humanities and Social Sciences, 2022)
The purpose of the study was to aware students about hand hygiene and also aware them about the negative effects of washing hands without soap. Students of public primary school were the population of the study. The school was selected by means of convenient sampling while participants were selected by purposive sampling. So, for the purpose seminar have been conducted to make students aware about hand cleanliness. One week different activities were conducted to make students habitual and adopt the habits ofwashing hands in their daily routine and in their schools after playing games and after using washroom. Pre and post intervention views have been taken from the teachers and students. Views of the participants indicated that organizing the seminar with practical activities was an effective practice to create awareness among students regarding hands cleanliness. This was a novel study as it explored the basic hygiene issues at primary level and proposed a solution through intervention. The awareness created by this study will be useful for the general health improvement of students. It will make teachers realize the importance and advantages of hygiene for general health of students.